Metode Tafsir An-Nasafī dalam Penafsiran Ayat-Ayat Syariat dan Akhlak Serta Sikapnya Terhadap Riwayat Isrā’īliyyāt - Aina Lestari Okika Sinaga; Muhammad Rusdi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study aims to analyze the exegetical method of Imam An-Nasafī in interpreting Qur’anic verses related to sharīʿah and ethics (akhlāq), as well as to examine his stance toward Isrā’īliyyāt narrations in the work Madārik al-Tanzīl wa Ḥaqā’iq al-Ta’wīl. The research employs a qualitative approach with a library research design. Primary data are derived from An-Nasafī’s tafsīr, while secondary data consist of classical and contemporary tafsīr books, academic journals, and relevant previous studies. Data were collected through documentation techniques, and analysis was conducted using content analysis and descriptive-analytical methods to identify the characteristics of An-Nasafī’s interpretive approach and the consistency of his thought. The findings reveal that An-Nasafī’s method of interpretation is integrative, combining the taḥlīlī approach with tafsīr bi al-ma’thūr and tafsīr bi al-ra’y. In interpreting sharīʿah verses, An-Nasafī emphasizes juridical aspects grounded in Islamic jurisprudence while linking them to moral and spiritual objectives such as piety, justice, and social welfare. In contrast, in interpreting ethical verses, he highlights inner moral values such as sincerity (ikhlāṣ) and gratitude (shukr) as the core of religious practice. Regarding Isrā’īliyyāt, An-Nasafī adopts a critical and selective stance, accepting only those narrations that do not contradict the Qur’an and Islamic creed. These findings indicate that An-Nasafī’s tafsīr offers a balanced understanding of the Qur’an by integrating legal and ethical dimensions and contributes significantly to the classical tradition of Qur’anic exegetical methodology